Analisis Responsibilitas Sub Humas Protokol dalam Publikasi Kegiatan DRRD Provinsi Jawa Timur - Innike Fitra Farastutie; Agus Widiyarta (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is motivated by the work responsibilities of employees at the East Java DPRD Secretariat in the Sub Public Relations Protocol section which is seen from how government administrators exercise their authority. Responsibility is a crucial foundation for government performance and legitimacy. The DPRD Secretariat is a government institution that supports all activities of the East Java DPRD. The Protocol Sub Public Relations role is to facilitate and publicize the activities of the East Java Province DPRD. The aim of this research is to find out how responsive the Sub-Public Relations Protocol is in carrying out its duties and obligations, realizing quality and responsible performance so that it can achieve the desired goals and support the DPRD's duties optimally. This research uses a qualitative method with a descriptive approach. This research uses the Responsibility Parameter theory according to Jabra and Dwivedi, namely understanding responsibility, granting authority in accordance with responsibility, performance evaluation, accurate, fair, timely actions, and commitment from the leader. The results of this research found that the responsibility and responsibility of the Protocol Sub Public Relations section was very good. This can be seen from the results of the work achievements in that section, which has carried out its main duties and tasks well.